Penerapan Sistem Informasi Penggajian Terintegrasi Dengan Absensi Real-Time Berbasis Web Pada CV. The Three Points Menggunakan Metode SDLC (Software Development Life Cycle) - Dedy Chandra Wardani; Khairul Khairul; Jodi Hendrawan (LKP KARYA PRIMA KURSUS, 2025)
This study discusses the implementation of a web-based payroll information system integrated with real-time attendance at CV. The Three Points, using the SDLC (Software Development Life Cycle) method. The company's current payroll process is still carried out manually, leading to several issues such as payroll delays, calculation errors, and lack of transparency in employee attendance data. To address these problems, a system was developed to automate payroll processing and integrate it directly with real-time attendance data. The SDLC method was employed in the system development, consisting of planning, analysis, design, implementation, and maintenance stages. The system was built using web-based technology to ensure flexible access for the finance and management departments. The implementation results show that the system improves efficiency and accuracy in the payroll process and simplifies employee attendance monitoring. It also automatically generates payroll and attendance reports, accessible at any time by authorized users. With the integration of attendance and payroll data, salary calculations become faster and less error-prone. Additionally, the system supports increased transparency and accountability in the company’s human resource management. This study is expected to serve as a reference for other companies seeking to implement an effective and efficient integrated payroll information system